2015
DOI: 10.1063/1.4935856
|View full text |Cite
|
Sign up to set email alerts
|

Zero lattice mismatch and twin-free single crystalline ScN buffer layers for GaN growth on silicon

Abstract: We report the growth of thin ScN layers deposited by plasma-assisted molecular beam epitaxy on Sc2O3/Y2O3/Si(111) substrates. Using x-ray diffraction, Raman spectroscopy, and transmission electron microscopy, we find that ScN films grown at 600 degrees C are single crystalline, twin-free with rock-salt crystal structure, and exhibit a direct optical band gap of 2.2 eV. A high degree of crystalline perfection and a very good lattice matching between ScN and GaN (misfit < 0.1%) makes the ScN/Sc2O3/Y2O3 buffer sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This has led to avenues for the use of ScN as a dislocation reduction buffer layer, and for in-situ ohmic contacts for GaN based devices [20] . Earlier studies have reported the growth of binary ScN thin films by reactive magnetron sputtering, hydride vapor phase epitaxy, and gas-source and plasma MBE on Si, Al2O3, SiC, and MgO surfaces [21][22][23][24][25][26][27][28][29] . Very few reports exist of ScN epitaxy on GaN [30] , and no results have yet been shown for growth on AlN.…”
mentioning
confidence: 99%
“…This has led to avenues for the use of ScN as a dislocation reduction buffer layer, and for in-situ ohmic contacts for GaN based devices [20] . Earlier studies have reported the growth of binary ScN thin films by reactive magnetron sputtering, hydride vapor phase epitaxy, and gas-source and plasma MBE on Si, Al2O3, SiC, and MgO surfaces [21][22][23][24][25][26][27][28][29] . Very few reports exist of ScN epitaxy on GaN [30] , and no results have yet been shown for growth on AlN.…”
mentioning
confidence: 99%
“…Such metal/semiconductor metamaterials have demonstrated optical metamaterial properties and currently researched for thermionic energy conversion [37,38]. Similarly, because of their latticematched interface, (111) ScN interlayers have been used successfully to grow dislocation and defect-free (0001) GaN [39,40]. The high carrier concentration of ScN is further leveraged to excite low-loss and high-quality plasmon and phonon polaritons in the near and far infrared (IR) spectral ranges, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of these stripelike crystals with specific orientations is likely due to the formation of twinned crystals during the heteroepitaxy growth, which has been observed in many organic or inorganic epitaxy growth process. 40,41 Additionally, the evolution from terraced to stripelike morphology also implies the existence of a certain lattice mismatch between TIPS-PEN and TIPS-TAP, which triggers various morphologies with increasing thicknesses due to the stress relief. Furthermore, this heteroepitaxy growth strategy is applicable to other materials such as dif-TES-ADT and C 8 -BTBT (Figure S7), indicative of the promising application of this strategy for constructing diverse heterostructures.…”
mentioning
confidence: 99%